THE DETERMINANTS AND EFFECTS OF JICA RICE TECHNOLOGY ADOPTION IN THE SAGNARIGU DISTRICT OF THE NORTHERN REGION, GHANA - Zackaria, A; Ansah, I. G. K; Abdulai, S; Donkoh, S A (UDS International Journal of Development, 2016)
This study analysed the adoption of JICA rice production technologies and its effect on output in Sagnarigu District of the Northern Region. A total of 120 respondents from six communities in the Sagnarigu District were randomly selected and interviewed using semi-structured questionnaires. The logit model was used to determine the factors that influenced the adoption of JICA rice production technologies while the propensity score matching was employed to estimate the effect of treatment (adoption) on rice output. The study found that membership to farmer association and fertilizer subsidy positively and significantly influenced adoption of the rice production technologies whereas farm size, access to agricultural extension, use of other improved seed, and household size negatively affected adoption of the rice production technologies. The adoption of technologies led to a significant improvement in rice output. We recommend that farmers be supported to step up their adoption of the rice technologies through the formation of farmer groups as well as the fertilizer subsidization programme, among others. Keywords: Adoption, JICA, Propensity Score Matching, Rice, Technology